Exploring nurses' experiences of providing spiritual care to cancer patients: a qualitative study - Huda A. Anshasi; Mirna Fawaz; Yousef M. Aljawarneh; Ja'far M. Alkhawaldeh (BMC, 2024)
Abstract Purpose This study aims to explore nurses' experiences of delivering spiritual care in an oncology setting. Methods An exploratory- descriptive qualitative design. Focus groups were conducted to gather data. The discussions were recorded and transcribed verbatim to ensure accuracy, credibility, and reliability. Inductive thematic analysis was performed to analyze the narratives, and the study's reporting followed the Consolidated criteria for reporting qualitative studies. Results The study revealed four major themes: the spirituality from the perspective of oncology nurses, recognition of patients' spiritual needs, delivery of spiritual care to patients with cancer, and barriers in implementing spiritual care. The participants identified insufficient staff, lack of time, and insufficient knowledge and skills as obstacles to delivering spiritual care. Conclusion This study offers a thorough understanding of how nurses provide spiritual care in an oncology setting. It is recommended that organizational interventions, such as increasing staff numbers, be implemented to enable nurses to provide more compassionate care. Furthermore, nursing curriculums should incorporate purposeful engagement and focused debriefing related to spiritual care to better equip nurses in identifying and meeting the spiritual needs of their patients.